A new model for the tri-nitrogen EPR centre W21 in diamond - Baker, M (1999)
A new model is proposed For the centre in cape yellow type la diamonds, labelled W21, shown by its electron paramagnetic resonance spectrum to comprise three nitrogen atoms N.A planar structure in a {110} plane involving two vacancies V(N-V-N-V-N) is shown to be better able to account For all properties of the defect than the originally proposed model (N - N - N). Furthermore, this suggests that it is not possible to accommodate more than two adjacent substitutional nitrogen atoms in the diamond lattice without an adjacent vacancy.